THE EVALUATION OF ANTITHROMBOTIC TREATMENT PRESCRIPTION DYNAMICS IN PATIENTS WITH ATRIAL FIBRILLATION BY THE DATA OF PROFILE REGISTRY - S. Yu. Martsevich; A. R. Navasardian; N. P. Kutishenko; A. V. Zakharova; S. N. Tolpygina; V. P. Voronina; O. V. Lerman; N. A. Dmitrieva (Кардиоваскулярная терапия и профилактика)
Aim. As a part of outpatient registry PROFILE to study the thromboembolic risk (TER) according to CHA2DS2-VASc score, the structure and dynamics of antiplatelet drugs prescription for the patients with atrial fibrillation (AF) during two-year period (2012-2014). Material and methods. In the PROFILE registry the patients with AF were selected, requested medical assistance from 10.2013 till 06.2014 at specialized cardiological center. The visit was marked as Referent (RV). All patients (n=91) were retrospectively assessed using questionnaires, and medical data, and then they underwent the oral antithrombotic medication (OAM) evaluation that they had been receiving since 2012. Prospectively OAM therapy at the visit was evaluated by the data of medical documents filled: the main chart of a patient, included into PROFILE registry, and AF patient chart. The recommended therapy was analyzed.Results. During follow-up period there was relevant increase of OAM prescription to the patients with high TER and AF (p<0,05). In 2012 the OAM took 32,3% and in 2014 at RV — 63,8%. After RV to 84,6% patients the OAM were recommended. Increase of OAM prescription was found just by the novel OAM, warfarin prescription rate did not change: 25,6% in 2012 vs 24,2% at RV vs 20,9% of recommended during RV. Conclusion. Availability of novel OAM led to the increase of AF patients receiving OAM.